Decolorizing of seaweed extract by electrocoagulation - Winifred Akoetey; Simon Caton; Edward Lai; Farah Hosseinian (Food Production, Processing and Nutrition)
Abstract Electrocoagulation (EC) is a technique commonly used in wastewater treatment to remove biological and chemical contaminants, but the process has the potential to be used in clarifying plant extracts for the isolation and identification of secondary metabolites. Seaweed extracts contain copious amounts of chlorophyll and other pigments that obscure the characterization of secondary metabolites such as phenolic acids and flavonoids. In place of conventional methods that utilize solvents, EC can potentially be applied to clarify and fractionate extracts. In this research, an EC duration of 30 min (22 V, 0.3–0.5A) with aluminum electrodes resulted in a significant decrease, about 76%, of chlorophyll and 70% of carotenoids from seaweed extract measured at 666 nm and 410 nm. The decrease in extract green and yellow color intensity also mirrored a decrease in total phenolic content (TPC) of the extract from 54 ± 1.55 mg GAE/g DW to 3.2 ± 0.01 mg GAE/g DW after 30 min of EC. However, the phenolic acid profile of the extract after electrocoagulation via HPLC-RP indicated the removal of an interference probably caused by polymeric compounds from the extract, thus leaving the simple phenolic acids in solution for detection. The major phenolic acids detected in seaweed crude extract were p-coumaric, o-coumaric, ferulic and syringic acid. Flavonoids detected included catechin, epicatechin, quercetin-3-glucoside and rutin. The results of this study show the potential of replacing conventional plant extract purification methods with a green method that requires no additional solvent. Graphical Abstract